2021
DOI: 10.1684/ejd.2021.4010
|View full text |Cite
|
Sign up to set email alerts
|

Visualising the past to plan the future: a network analysis of the largest European dermatology conference

Abstract: Visualising the past to plan the future: a network analysis of the largest European dermatology conference Background: The annual conference of the European Academy of Dermatology and Venereology is one the largest dermatology conferences worldwide. Objectives: Network analysis can be used for in-depth insight into trending topics and underlying trends at the congress. Materials & Methods: Network analysis was employed to assess the entirety of the submitted abstracts to the congress in 2019. The data were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To visualise, analyse and structure the data, network analysis will be used to identify potential clusters within the large data sets. 31 Overall, the study aims to better understand the underlying mechanisms of AD and the interaction of various risk factors in infants to improve patient care and disease management.…”
Section: Strategic Aims For the Upcoming Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…To visualise, analyse and structure the data, network analysis will be used to identify potential clusters within the large data sets. 31 Overall, the study aims to better understand the underlying mechanisms of AD and the interaction of various risk factors in infants to improve patient care and disease management.…”
Section: Strategic Aims For the Upcoming Yearsmentioning
confidence: 99%
“…Combined with the already existing studies on individual risk factors on AD, we hope to expand on the evidence currently available in the literature and to identify areas which are hardly studied. To visualise, analyse and structure the data, network analysis will be used to identify potential clusters within the large data sets 31. Overall, the study aims to better understand the underlying mechanisms of AD and the interaction of various risk factors in infants to improve patient care and disease management.…”
Section: Strategic Aims For the Upcoming Yearsmentioning
confidence: 99%
“…For instance, network analysis has aided psychopathology in gaining a better understanding of mental illnesses by identifying symptom dynamics and revealing comorbidities [ 10 ]. As recent studies in dermatology have shown [ 11 , 12 ], there are many more opportunities that need to be exploited, especially for the analysis of text-based datasets.…”
Section: Introductionmentioning
confidence: 99%